Attraction of ambrosia beetles (Coleoptera: Scolytidae) to different tropical pine species in Brazil - Flechtmann, C. A.H. [UNESP]; Ottati, A. L.T. [UNESP]; Berisford, C. W. (Oxford University Press (OUP), 1999)
Ambrosia beetles are the predominant Scolytidae in Brazil. Little is known about the attractiveness of exotic conifer tree volatiles to native scolytids. Objectives were to compare the attractiveness of logs with and without bark of Pinus oocarpa Schiede, P. caribaea variety bahameasis Barrett and Golfari, P. car. variety caribaea Barrett and Golfari and P. car. variety hondurensis Barrett and Golfari over time to native scolytids in different pine stands, to compare the relative attractiveness of logs relative to ethanol traps, to determine how long it takes for logs to become attractive to ambrosia beetles and when attraction peaks occur, and to determine if volatiles released by live standing trees would mask volatiles released by logs of the same species. In young stands, Hypothenemus was the predominant insect genus, whereas in older stands Xyleborus predominated. Debarked logs trapped more beetles than logs with bark. Pine log species attractiveness was not influenced by volatiles present in the stand. Beetles were divided into the following 3 groups, based on response to log volatiles and ethanol: (1) species attracted to ethanol and not responding to pine terpenes Ambrosiodmus hagedorni (Iglesia), A. retusus (Eichhoff), X. spinulosus Blandford, Corthylus schaufussi Schiede, Cryptocarenus heveae (Hagedorn), H. obscurus (F.), (2) species attracted to ethanol but responding to pine terpenes Xyleborinus gracilis (Eichhoff), X. affinis Eichhoff, H. eruditus Westwood, Premnobius cavipennis Eichhoff, and (3) species more attracted to pine terpenes and less responsive to ethanol, A. obliquus (Le Conte), X. ferrugineus F., X. catulus Blandford. Pinus car. variety bahamensis was the least attractive pine, P. oocarpa the most attractive. The attraction peak varied according to the season; logs were not attractive to beetles 10 wk after cutting.
Keywords: Ambrosia beetles; Attractiveness peak; Pine terpenes versus ethanol response; Primary attraction; Tropical pines